Bimetallic Ag‐Pt Sub‐nanometer Supported Clusters as Highly Efficient and Robust Oxidation Catalysts. (29th December 2017) - Negreiros, Fabio R.; Halder, Avik; Yin, Chunrong; Singh, Akansha; Barcaro, Giovanni; Sementa, Luca; Tyo, Eric C.; Pellin, Michael J.; Bartling, Stephan; Meiwes‐Broer, Karl‐Heinz; Seifert, Sönke; Sen, Prasenjit; et al.
Abstract: A combined experimental and theoretical investigation of Ag‐Pt sub‐nanometer clusters as heterogeneous catalysts in the CO→CO2 reaction (COox) is presented. Ag9 Pt2 and Ag9 Pt3 clusters are size‐selected in the gas phase, deposited on an ultrathin amorphous alumina support, and tested as catalysts experimentally under realistic conditions and by first‐principles simulations at realistic coverage. In situ GISAXS/TPRx demonstrates that the clusters do not sinter or deactivate even after prolonged exposure to reactants at high temperature, and present comparable, extremely high COox catalytic efficiency. Such high activity and stability are ascribed to a synergic role of Ag and Pt in ultranano‐aggregates, in which Pt anchors the clusters to the support and binds and activates two CO molecules, while Ag binds and activates O2, and Ag/Pt surface proximity disfavors poisoning by CO or oxidized species.